BIOQUÍMICA NO TABULEIRO: MELHORIAS NO PROCESSO DE ENSINO APRENDIZAGEM NA EDUCAÇÃO BÁSICA - Silva, Fábio Augusto da (2016)
Facing the transformation of conceptual and methodological issues that the process of teaching and learning in Biology is suffering, differentiated teaching resources as input for the classes are increasingly being used. For exemple, there are educational games that allow the integration of theory and practice are effective, concrete and can enable learning becomes significant. This work aims to build a board game with the Biochemistry contents for the high school, according to the Curriculum Biology Education Guidelines (Diretrizes Curriculares Estaduais - DCEs) (2008), and aims to map the specific contents of Biochemistry taught by teachers in basic education in an attempt to improve the teaching and learning process of these contents. The game Biochemistry on the Table was based on the game called Perfil, from Grow. It consists of 37 cards with concepts related to the biochemistry content, and have tips for players to answer in a correct way, increase their scores and reach the end of the trail. This is an applied research, the case study type, predominantly qualitative-interpretative. Data analysis has involved the contextualization and interpretation of the classroom setting and their contexts. The tools of data collection were semi-structured questionnaire (profile of teachers, pre-test, post-test, game evaluation), desk research and field diary. The research subjects were teachers and high school students of State School Alba Keinerth, from Guarapuava - PR. It was found that the teachers do not use games in the classroom, but believe that their methodology is significant for the Biology teaching. They showed that the greatest difficulties of teaching Biochemistry in basic education is the lack of literature, lack laboratory and conceptual gaps in their own training graduation. The content buffering systems is not worked for any of the teachers. In the evaluation of the game, both teachers and students say the methodology is valid and assists in the learning process of the topics covered in the classroom.